Climate Extremes and Society - Diaz, Henry F (Cambridge University Press, 2013)
This book summarizes our knowledge of different aspects of weather and climate extremes and then focuses on their recent and potential future consequences for different socioeconomic sectors. We also examine some actions that may enable us to better respond to and adapt to climate variability regardless of its source – for example, the development of public–private research and applications partnerships, and the development of statesupported public hurricane risk models for decision support